Clinical Lycanthropy, Neurobiology, Culture: A Systematic Review - Guessoum, Sélim Benjamin; Benoit, Laelia; Minassian, Sevan; Mallet, Jasmina; Moro, Marie Rose (Frontiers in Psychiatry, 2021)
Background: Culture can affect psychiatric disorders. Clinical Lycanthropy is a rare syndrome, described since Antiquity, within which the patient has the delusional belief of turning into a wolf. Little is known on its clinical or therapeutic correlates. Methods: We conducted a systematic review (PRISMA) on Pubmed and GoogleScholar, until January 2021. Case reports, data on neurobiological hypotheses, and cultural aspects were included. Language was not restricted to English. Results: 43 cases of clinical lycanthropy and kynanthropy (delusion of dog transformation) were identified. Associated diagnoses were: schizophrenia, psychotic depression, bipolar disorder, and other psychotic disorders. Antipsychotic medication may be an efficient treatment for this rare transnosographic syndrome. In case of depression or mania, the treatment included antidepressants or mood regulators. The neuroscientific hypotheses include the conception of clinical lycanthropy as a cenesthopathy, as a delusional misidentification of the self-syndrome, as impairments of sensory integration, as impairments of the belief evaluation system, and right hemisphere anomalies. Interestingly, there is a clinical overlap between clinical lycanthropy and other delusional misidentification syndromes. Clinical lycanthropy may be a culture-bound syndrome that happens in the context of Western cultures, myths, and stories on werewolves, and today’s exposure to these narratives on cultural media such as the internet and the series. We suggest the necessity of a cultural approach for these patients’ clinical assessment, and a narrative and patient-centered care. Conclusions: Psychiatric transtheoretical reflections are needed for complementaristic neurobiological and cultural approaches of complex delusional syndromes such as clinical lycanthropy. Future research should include integrative frameworks.